1999
DOI: 10.4141/a98-099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous enzymes on digestibility of barley silage and growth performance of feedlot cattle

Abstract: . 1999. Effect of exogenous enzymes on digestibility of barley silage and growth performance of feedlot cattle. Can. J. Anim. Sci. 79: 353-360. Barley silage was sprayed with water or with a 2:1 combination of commercial cellulase and xylanase preparations, or the enzymes were introduced directly into the rumen, in a digestibility study (replicated incomplete 3 × 3 Latin square) using 10 sheep. Apparent digestibilities of dry matter (DM) and neutral detergent fibre (NDF) were lower (P < 0.05) when enzymes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
41
1
12

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 21 publications
10
41
1
12
Order By: Relevance
“…Although most of the published literature have reported increased total tract digestibility of DM, OM or both following treatment with a fibrolytic enzyme mixture (e.g., Rode et al, 1999;Yang et al, 1999;Beauchemin et al, 2000), other studies have reported no effect of exogenous fibrolytic enzyme on digestibility DM or OM (e.g., Lewis et al, 1999;McAllister et al, 1999McAllister et al, , 2000Yang et al, 2000) in agreement with the current study. In the present study, the elevated DM and OM intakes and unchanged apparent digestibility coefficient of the diet (Table 2) was probably accompanied by faster rate of ruminal and total tract rate of passage.…”
Section: Resultssupporting
confidence: 90%
“…Although most of the published literature have reported increased total tract digestibility of DM, OM or both following treatment with a fibrolytic enzyme mixture (e.g., Rode et al, 1999;Yang et al, 1999;Beauchemin et al, 2000), other studies have reported no effect of exogenous fibrolytic enzyme on digestibility DM or OM (e.g., Lewis et al, 1999;McAllister et al, 1999McAllister et al, , 2000Yang et al, 2000) in agreement with the current study. In the present study, the elevated DM and OM intakes and unchanged apparent digestibility coefficient of the diet (Table 2) was probably accompanied by faster rate of ruminal and total tract rate of passage.…”
Section: Resultssupporting
confidence: 90%
“…Digestion of plant cell walls, which is carried out by ruminal microorganisms, provides a large amount of energy for ruminants. Fibrolytic enzymes isolated from fungi fermentation cultures have been utilized to improve DMI and forage digestibility; particulate passage rate; and digestibility of DM, NDF, and ADF in beef steers (McAllister et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…McAllister et al (1999), avaliando o desempenho de novilhos em confinamento, observaram aumentos de 5,99 kg/dia para 6,72 kg/dia na ingestão de MS e de 0,94 kg/dia para 1,16 kg/dia no ganho médio diário com a suplementação enzimática (celulase e xilanase). Lewis et al (1995), em estudo com vacas em lactação consumindo forragem, também verificaram aumentos de 5 a 25% no consumo e na produção de leite com a adição de enzimas fibrolíticas exógenas na dieta.…”
Section: Introductionunclassified